A wafer-scale Bernal-stacked bilayer graphene film obtained on a dilute Cu (0.61 at% Ni) foil using atmospheric pressure chemical vapour deposition. Issue 34 (17th March 2016) - Madito, M. J.; Manyala, N.; Bello, A.; Dangbegnon, J. K.; Masikhwa, T. M.; Momodu, D. Y.
Abstract : A wafer-scale (scale of an entire foil) AB-stacked bilayer graphene film obtained on a dilute Cu(Ni) foil using AP-CVD. Abstract : A bilayer graphene film was synthesized on a dilute Cu (0.61 at% Ni) foil using atmospheric pressure chemical vapour deposition (AP-CVD). Atomic force microscopy average step height analysis, scanning electron microscopy micrographs and the Raman optical microscopy images and spectroscopy data supported by selected area electron diffraction data showed that the bilayer graphene film obtained on a dilute Cu (0.61 at% Ni) foil is of high-quality, continuous over a wafer-scale (scale of an entire foil) and mainly Bernal stacked. These data clearly showed the capability of a dilute Cu (0.61 at% Ni) foil for growing a wafer-scale bilayer graphene film. This capability of a dilute Cu (0.61 at% Ni) foil was ascribed primarily to the metal surface catalytic activity of Cu and Ni catalyst. A wafer-scale bilayer graphene film obtained on a dilute Cu (0.61 at% Ni) foil has a sheet resistance of 284 Ω sq −1 (measured using a four-point probe station). Time-of-flight secondary ion mass spectrometry and X-ray photoelectron spectroscopy showed a high surface concentration of Ni in the dilute Cu (0.61 at% Ni) foil which altered the surface catalytic activity of the Cu to grow a wafer-scale bilayer graphene film.